Freshwater sponges in the southeastern U.S. harbor unique microbiomes that are influenced by host and environmental factors - Jacqueline G. Keleher; Taylor A. Strope; Noah E. Estrada; Allison M. Griggs Mathis; Cole G. Easson; Cara Fiore (PeerJ)
Marine, and more recently, freshwater sponges are known to harbor unique microbial symbiotic communities relative to the surrounding water; however, our understanding of the microbial ecology and diversity of freshwater sponges is vastly limited compared to those of marine sponges. Here we analyzed the microbiomes of three freshwater sponge species: Radiospongilla crateriformis, Eunapius fragilis, and Trochospongilla horrida, across four sites in western North Carolina, U.S.A. Our results support recent work indicating that freshwater sponges indeed harbor a distinct microbiome composition compared to the surrounding water and that these varied across sampling site indicating both environmental and host factors in shaping this distinct community. We also sampled sponges at one site over 3 months and observed that divergence in the microbial community between sponge and water occurs at least several weeks after sponges emerge for the growing season and that sponges maintain a distinct community from the water as the sponge tissue degrades. Bacterial taxa within the Gammproteobacteria, Alphproteobacteria, Bacteroidota (Flavobacteriia in particular), and Verrucomicrobia, were notable as enriched in the sponge relative to the surrounding water across sponge individuals with diverging microbial communities from the water. These results add novel information on the assembly and maintenance of microbial communities in an ancient metazoan host and is one of few published studies on freshwater sponge microbial symbiont communities.